The Hotspot for (Global) One Health in Primary Food Production: Aflatoxin M1 in Dairy Products - Frazzoli, Chiara; Gherardi, Paola; Saxena, Navneet; Belluzzi, Giancarlo; Mantovani, Alberto (Frontiers in Public Health, 2017)
One health involves the multifaceted environment-animal-human web: nevertheless, the role of toxicological issues has yet to be fully explored in this context. Aflatoxin B1contamination of feeds is a risk for the health of several farm animals, including fishes; milk is the only food of animal origin where a significant feed-food carry over may occur. The main AFB1-related compound present in milk is the hydroxy-metabolite aflatoxin M1 (AFM1). Besides contamination of raw milk, AFM1 is of concern for the whole dairy chain; AFM1 may also contaminate the milk of several other ruminants used for milk/dairy production. In a One Health perspective, milk represents a sentinel matrix for AFB1 vulnerability of the agro-food system, that is crucial in a phase when food/nutritional security becomes a global issue and climatic changes may affect agricultural productions. In the global setting, food-chain exposure to long-term toxicants, such as AFM1, is a growing concern for economically developing countries, whereas global trade and climatic change makes AFM1 a emerging hot issue in economically developed countries as well. We critically review the state of the art on AFM1 risk assessment and risk management using two scenarios as case studies: a European Union country where the health system aims at ensuring a high-level protection of food chain (Italy) and the world’s largest (and economically developing) producer of dairy products by volume (India). The case studies are used to provide building blocks for a global one-health framework.